Mr - Njuguna, Alex M (2010)
Abstract Although acculturation studies have vastly been conducted in the United States, there has been little research work conducted in other cultural societies such as the United Kingdom. Previous works on acculturation have also not exhaustively looked at how immigrant groups are influenced in their consumption patterns by a sub-cultural group with most works focusing on the dominant and the original culture perspectives. In response, this study examines the role and influence of the Black British as a sub-cultural group living in the United Kingdom and how this group influences the consumption practises of Kenyan immigrants. Findings reveal that Kenyan immigrants consumption practises are not directly influenced by the Black British sub culture and these findings are in stark contrast to a similar study carried out in the United states that established that Kenyan immigrants need to acculturate to the African American sub cultural group in order to access basic consumption services such as Hair care, Night club entertainment and Church services.